Plaques and tangles and the pathogenesis of Alzheimer’s disease - A. Armstrong, Richard (Folia Neuropathologica, 2006)
Since the earliest descriptions, senile plaques (SP) and neurofibrillary tangles (NFT) have been regarded as the pathological hallmarks of Alzheimer’s disease (AD). Consequently, studies of the morphology, distribution, and molecular composition of SP and NFT have played an important role in developing theories as to the pathogenesis of AD; the most important being the ‘Amyloid Cascade Hypothesis (ACH)’. Nevertheless, the significance of SP and NFT to the pathogenesis of AD remains controversial. This review examines three questions: 1) is there a relationship between the lesions and the degree of clinical dementia, 2) is the pathogenesis of the NFT linked to that of the SP, and 3) what is the relationship of SP and NFT to the pathogenesis of AD? These questions are discussed with reference to the morphology and molecular composition of SP and NFT, the effects of gene mutations, studies of head injury patients, experimental studies involving brain lesions and transgenes, and the degeneration of specific anatomical pathways. It was concluded that SP and NFT are not closely related to the developing dementia in AD, arise as relatively independent lesions, and may be the products of a degenerative process rather than being their cause.